Genome editing of mutant KRAS through supramolecular polymer-mediated delivery of Cas9 ribonucleoprotein for colorectal cancer therapy - Wan, Tao; Chen, Yuxuan; Pan, Qi; Xu, Xiaojie; Kang, Yu; Gao, Xue; Huang, Feihe; Wu, Chuanbin; Ping, Yuan (Journal of controlled release, 2020)
CRISPR (clustered, regularly interspaced, short palindromic repeats)/CRISPR-associated protein 9 (Cas9) system has emerged as a powerful genome-editing tool to correct genetic disorders. However, successful intracellular delivery of CRISPR/Cas9, especially in the form of ribonucleoprotein (RNP), remains elusive for clinical translation. Herein, we describe a supramolecular polymer that can mediate efficient controlled delivery of Cas9 RNP in vitro and in vivo. This supramolecular polymer system is prepared by complexing disulfide-bridged biguanidyl adamantine (Ad-SS-GD) with β-cyclodextrin-conjugated low-molecular-weight polyethyleneimime (CP) through supramolecular assembly to generate CP/Ad-SS-GD. Due to multiple, strong hydrogen bonding and salt bridge effects, CP/Ad-SS-GD well interact with Cas9 RNP to form stable nanocomplex CP/Ad-SS-GD/RNP, which can be readily released in the reductive intracellular milieu as a result of the cleavage of disulfide bonds. The supramolecular polymer ensures the efficient intracellular delivery and the release of Cas9 RNP into 293T cells and colorectal cancer (CRC) cells, thus displaying high genome-editing activity in vitro. Importantly, we also found that hyaluronic acid (HA)-decorated CP/Ad-SS-GD/RNP nanocomplexes targeting mutant KRAS effectively inhibit tumor growth as well as metastasis in the tumor-bearing mouse models. Collectively, our findings provide a promising therapeutic strategy against mutant KRAS for the treatment of CRC-activated RAS pathways, offering a new therapeutic genome-editing modality for the colorectal cancer treatment. [Display omitted]